Development of speed-strength qualities of boys doing karate (Bangladesh Journal of Medical Science, 2026)
Aim is to increase the level of development of speed-strength abilities of 13-14-year-old boys who do karate. Material and methods The pedagogical experiment was conducted in 2024 at the Moscow Olympic Reserve Sports School, the Karate department. The study involved 68 boys aged 13-14. Classes in the karate section were held 3 times a week for 90 minutes. The speedstrength qualities of the core muscles were determined by lifting the body in the sitting position for 1 minute, the speed-strength qualities of the leg muscles were determined using the shuttle run 3*10 m, and the speed-strength qualities of the arm muscles were determined using the test of flexion and extension of the arms in the prone position for 1 minute. Results After the pedagogical experiment, the speed-strength qualities of the 13-14-year-old children participating in the study increased in both groups. Children from the control group, who trained according to the standard program, increased their core muscle indicators from 43.4±5.1 to 46.7±4.1, the increase is 7.1% (p>0.05), in the shuttle run test the indicators improved by 8.3% from 9.1±0.8 to 8.4±0.6 (p>0.05), and the speed-strength qualities of the arms became higher by 8.8%, the average results increased from 19.8±4.2 to 21.7±3.9 (p>0.05). Children from the experimental group, who also trained according to the standard karate program, but at the same time performed special sets of physical exercises for 20 minutes after the warmup, were able to significantly improve their speed-strength qualities. The core muscle indices increased from 42.2±3.9 to 48.9±4.6, the increase is 13.7% (p